Effects of bepridil on early cardiac development of zebrafish - Ya-Lan Wei; Yu-Qing Lei; Zhou-Jie Ye; Xu-Dong Zhuang; Li-Ping Zhu; Xin-Rui Wang; Hua Cao (Cell and Tissue Research, 2023)

Crosstalk between exosomes and autophagy in spinal cord injury: fresh positive target for therapeutic application - Rui-yu Li; Qi Hu; Xu Shi; Zhen-yu Luo; Dong-hua Shao (Cell and Tissue Research, 2023)
Spinal cord injury (SCI) is a very serious clinical traumatic illness with a very high disability rate. It not only causes serious functional disorders below the injured segment, but also causes unimaginable economic burden to social development. Exosomes are nano-sized cellular communication carriers that exist stably in almost all organisms and cell types. Because of their capacity to transport proteins, lipids, and nucleic acids, they affect various physiological and pathological functions of recipient cells and parental cells. Autophagy is a process that relies on the lysosomal pathway to degrade cytoplasmic proteins and organelles and involves a variety of pathophysiological processes. Exosomes and autophagy play critical roles in cellular homeostasis following spinal cord injury. Presently, the coordination mechanism of exosomes and autophagy has attracted much attention in the early efficacy of spinal cord injury. In this review, we discussed the interaction of autophagy and exosomes from the perspective of molecular mechanisms, which might provide novel insights for the early therapeutic application of spinal cord injury.

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

TGF-β1-modified MSC-derived exosomal miR-135b attenuates cartilage injury via promoting M2 synovial macrophage polarization by targeting MAPK6 - Rui Wang; Bin Xu (Cell and Tissue Research, 2021)

Gene expression profile of campylobacter jejuni-induced GBS in bama miniature pigs - Feng Xue; Dexin Zeng; Fei Xu; Rui Zhang; Yang Chen; Yuefei Yang; Xiaobo Wang; Zhenzhong Li; Xiaorong Zhang; Yuan Jiang (Cell and Tissue Research, 2012)

Characterization of a novel isoform of the human ORMDL3 gene - Rui Jin; Wen-Xiao Yuan; Hua-Guo Xu; Wei Ren; Li-Li Zhuang; Guo-Ping Zhou (Cell and Tissue Research, 2011)

Expression of thyrotropin-releasing hormone receptors in rat testis and their role in isolated Leydig cells - Yong Zhao; Wu-Gang Hou; Hua-Ping Zhu; Jie Zhao; Rui-An Wang; Ruo-Jun Xu; Yuan-Qiang Zhang (Cell and Tissue Research, 2008)